Interaction of squalamine with lipid membranes - Grage, Stephan L.; Guschtschin-Schmidt, Nadja; Meng, Beibei; Kohlmeyer, Annika; Afonin, Sergii; Ulrich, Anne S. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2025)
Squalamine is an aminosterol from dogfish shark which has drawn attention, besides its antimicrobial activity, as a drug candidate in the treatment of Parkinson’s disease due to its ability to prevent binding of α-synuclein to lipid membranes. To get insight into the mode of action of this steroid, we studied the influence of squalamine on lipid bilayers and whether it could inhibit the binding of a model peptide. Solid-state 19F NMR of labeled [KIGAKI]3 indicated that, indeed, this peptide no longer binds as a flexible chain to the bilayer in the presence of squalamine. When the cationic squalamine was added to lipid vesicles containing phosphatidylglycerol lipids, the aminosterol was found in differential scanning calorimetry and solid-state 31P NMR experiments to lower the gel-to-fluid phase transition and cause the phase separation of domains enriched in anionic lipids. Squalamine had only a little influence on 2H NMR relaxation and on the order parameters of the chains. These findings indicate that the aminosterol does not affect the molecular mobility of the hydrophobic core of the bilayer; hence, it does not insert into the membrane, nor causes thinning as found for molecules inserting in the headgroup region. On the other hand, squalamine was found to interact with lipid headgroups through electrostatic interactions, as seen by solid-state 2H NMR on headgroup-labeled lipids. Furthermore, 31P NMR showed that squalamine shifted the lamellar-to-hexagonal phase transition of phosphatidylethanolamine lipids to higher temperatures, indicating a preference for positively curved membranes. Altogether, our experiments indicate a strong interaction of the cationic squalamine with lipid headgroups, in particular with anionic lipids. This affinity for membranes is strong enough to efficiently displace cationic polypeptides, confirming the proposed action mechanism in Parkinson treatment. Notably, supported by 1H-1H NOESY experiments, it was found that squalamine does not insert into the bilayer, but rather acts as facial amphiphile binding to the membrane surface. The binding to membranes may be envisaged in the form of oligomeric or micellar assemblies, which can disrupt the membrane at high concentrations, thereby explaining the antimicrobial and antifungal activities of squalamine.
Online veröffentlicht: 5. Februar 2025
Gesehen am 25.07.2025